PECULIARITIES OF THE FORMATION OF SENSORIMOTOR PROCESSES IN CHILDREN WITH MENTAL DEVELOPMENT PROBLEMS - Khudoyberdiyeva Ra’no Arabboevna (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the specificity of the formation of sensorimotor processes of children with mental development problems, its generalizing functions, goal-oriented sensory education and reflection of objects and events as a result of direct impact on their sensory organs are covered.